The effect of self-care behaviors education on quality of life in patients with type 2 diabetes: a randomized clinical trial - Towhid Babazadeh; Amin Kiani; Fatemeh Moradi; Fariba Shariat; Morteza Banaye Jeddi (Fasa University of Medical Sciences, 2016)
Background & Objectives: Diabetes is the most common metabolic disorder which if not controlled; it can cause a decrease in patient's quality of life. Therefore, this study was carried out to evaluate the effect of educational intervention of self-care behaviors on quality of life in patients with type 2 diabetes. Materials and methods: This clinical trial study was conducted in 2015 on 90 patients with Type II diabetes in the city Chalderan. Patients were stratified randomization to intervention and control groups. Data was collected using standardized questionnaires in two phases before and 3 month after the educational. To analyze the data was used descriptive statistics and paired t and independent t tests in level of p<0.05. Results: Mean and standard deviation age of the patients was 46.3 ± 9.5. The results showed that the mean (SD) score of knowledge, attitudes and self-care behaviors significantly has increased in intervention group, but changes was not significant in the control group. Also, the educational intervention had a significant effect in improving the quality of life in all its dimensions compared to the control group had (p<0.05). Conclusion: The findings of current study showed that educational intervention has been improved self-care behaviors in patients with type II diabetes. Also the results showed that by training self-care behaviors can be improved quality of life.